After Deportation Ethnographic Perspectives (Global Ethics, 2018)
This book analyses post-deportation outcomes and focuses on what happens to migrants and failed asylum seekers after deportation. Although there is a growing literature on detention and deportation, academic research on post-deportation is scarce. The book produces knowledge about the consequences of forced removal for deportee's adjustment and "reintegration" in so-called "home" country. As the pattern of migration changes, new research approaches are needed. This book contributes to establish a more multifaceted picture of criminalization of migration and adds novel aspects and approaches, both theoretically and empirically, to the field of migration research.